The Slippery Slope : Explaining the Increase in Extreme Poverty in Urban Brazil, 1976 96 - Barros, de Paes Ricardo (The World Bank, 1999)
October 1999 - During the turbulent years 1976-96, aggregate data for Brazil appear to show only small changes in mean income, inequality, and incidence of poverty - suggesting little change in the distribution of income. But a small group of urban households - excluded from formal labor markets and safety nets - was trapped in indigence. Based on welfare measured in terms of income alone, the poorest part of urban Brazil has experienced two lost decades. Despite tremendous macroeconomic instability in Brazil, the country's distributions of urban income in 1976 and 1996 appear, at first glance, deceptively similar. Mean household income per capita was stagnant, with minute accumulated growth (4.3 percent) over the two decades. The Gini coefficient hovered just above 0.59 in both years, and the incidence of poverty (relative to a poverty line of R